Cryopreservation of Adenium obesum seeds in liquid nitrogen - Rosa, Talita Angélica de Oliveira; Pedro Junior, Sérgio; Tejo, Débora Perdigão; Paula, Jean Carlo Baudraz de; Shimizu, Gabriel Danilo; de Faria, Ricardo Tadeu (Pesquisa Agropecuaria Brasileira, 2024)
The objective of this work was to evaluate cryoprotectants on the physiological quality of Adenium obesum seeds preserved in liquid nitrogen. The following treatments were used: T1, control, without cryoprotectant and without immersion in liquid nitrogen; T2, with immersion in liquid nitrogen and without cryoprotectant; T3, with 0. 4 mol L-1 sucrose; T4, with 0.8 mol L-1 sucrose; T5, with 1.0 mol L-1 glycerol; T6, with 2.0 mol L-1 glycerol with PVS1; T7, with PVS1; T8, with PVS2; T9, with PVS2 + phloroglucinol (modified PVS2); and T10, with PVS3. Adenium obesum seeds show tolerance to immersion and storage in liquid nitrogen and do not need cryoprotectants to maintain their physiological quality when stored in a water content of 7.5%.